20 In vivo tracking of human pluripotent stem cell vascular derivatives. (20th November 2012) - Low, L; Cheung, C; Bennett, M; Sinha, S
Abstract : There is compelling in vivo evidence that the inclusion of mural cells in addition to endothelial cells (ECs) can augment the formation of functional blood vessels in therapeutic angiogenesis. However, it remains unclear whether CD34+ vascular progenitor cells, which have the potential to differentiate into both ECs and vascular smooth muscle cells (VSMCs), are superior to fully differentiated VSMCs at supporting revascularisation. In addition, it would be of interest to determine whether VSMCs from different embryological origins have differential influences on vessel development. To address these questions, we have developed chemically-defined protocols to differentiate human embryonic stem cells (hESCs) to CD34+ progenitors, ECs and origin-specific SMCs. In order to overcome the challenge of tracking the fate of these cells in vivo, a stably transduced hESC line (C4) that expresses mStrawberry and luciferase has been created. This cell line retains its pluripotency and thus its ability to differentiate into the vascular derivatives, without compromising efficiency or expression of mStrawberry and luciferase. In an in vivo pilot study, C4 hESCs were successfully visualised by bioluminescence imaging up to 2 hours after subcutaneous injection into Rag2 mice. However, at 24 hours the cells were no longer detectable. Although Rag2 mice are immunocompromised, they retain natural killer cells, which may be responsible for the apparent cell death. Further in vivo optimisation is planned, using alternative immunodeficient mice, to establish a model in which the revascularisation potential of hESC-derived vascular progenitors and cells can be assessed in vivo.